Cytokine regulation by virus infection: Bovine viral diarrhea virus, a flavivirus, downregulates production of tumor necrosis factor alpha in macrophages in vitro - Adler, H.; Jungi, T.W.; Pfister, H.; Strasser, M.; Sileghem, M.R.; Peterhans, E. (1996)
Bovine bone marrow-derived macrophages were infected in vitro with non-cytopathic or cytopathic strains of bovine viral diarrhoea virus. Infection with both biotypes resulted in a decreased production of tumour necrosis factor alpha upon stimulation with heat-inactivated Salmonella dublin or lipopolysaccharide. Other macrophage functions were not downregulated, indicating that the observed effect was not due to a loss in macrophage viability. The downregulated production of tumour necrosis factor alpha in infected macrophages may contribute to the well-documented immunosuppression in animals infected with bovine viral diarrhoea virus.